Prevalence and incidence of postpartum depression and environmental factors: The IGEDEPP cohort. (June 2021) - Tebeka, Sarah; Le Strat, Yann; De Premorel Higgons, Alix; Benachi, Alexandra; Dommergues, Marc; Kayem, Gilles; Lepercq, Jacques; Luton, Dominique; Mandelbrot, Laurent; Ville, Yves; Ramoz, Nicolas; Tezenas du Montcel, Sophie; et al.
Abstract: Background: IGEDEPP (Interaction of Gene and Environment of Depression during PostPartum) is a prospective multicenter cohort study of 3310 Caucasian women who gave birth between 2011 and 2016, with follow-up until one year postpartum. The aim of the current study is to describe the cohort and estimate the prevalence and cumulative incidence of early and late-onset postpartum depression (PPD). Methods: Socio-demographic data, personal and family psychiatric history, as well as stressful life events during childhood and pregnancy were evaluated at baseline. Early and late-onset PPD were assessed at 8 weeks and 1 year postpartum respectively, using DSM-5 criteria. Results: The prevalence of early-onset PPD was 8.3% (95%CI 7.3–9.3), and late PPD 12.9% (95%CI 11.5–14.2), resulting in an 8-week cumulative incidence of 8.5% (95%CI 7.4–9.6) and a one-year cumulative incidence of PPD of 18.1% (95%CI: 17.1–19.2). Nearly half of the cohort (N = 1571, 47.5%) had a history of at least one psychiatric or addictive disorder, primarily depressive disorder (35%). Almost 300 women in the cohort (9.0%) reported childhood trauma. During pregnancy, 47.7% women experienced a stressful event, 30.2% in the first 8 weeks and 43.9% between 8 weeks and one year postpartum. Nearly one in five women reported at least one stressful postpartum event at 8 weeks. Conclusion: Incident depressive episodes affected nearly one in five women during the first year postpartum. Most women had stressful perinatal events. Further IGEDEPP studies will aim to disentangle the impact of childhood and pregnancy-related stressful events on postpartum mental disorders.